Innovation Revolution and Entrepreneurial Finance: Transforming the Performance of Businesses beyond Traditional Boundaries - Mastan, Stanislaus Adnanto; Radianto, Wirawan Endro Dwi; Henryanto, Aria Ganna (Jurnal Aplikasi Manajemen, 2025)
Micro, small, and medium enterprises (SMEs) serve as the backbone of Indonesia’s economy, and their performance requires continuous strengthening because family-owned businesses dominate the sector and face persistent challenges in managing innovation and financial resources. This study aims to analyze the influence of innovation and entrepreneurial finance on business performance, particularly within family-owned SMEs in Indonesia, where family-owned businesses dominate the sector and face persistent challenges in managing innovation and financial resources, creating a strategic question about how these two factors jointly affect business performance. The study adopts a quantitative approach, distributing structured questionnaires to 309 SME owners and managers across multiple sectors, and uses purposive sampling to capture diverse business conditions. The data are examined using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate both measurement and structural models. The findings demonstrate that innovation exerts a significant positive effect on business performance and that entrepreneurial finance strengthens this effect by mediating the relationship between innovation and performance. The study contributes novelty by integrating the Resource-Based Theory with entrepreneurial finance to explain SMEs’ sustainability, and it provides practical implications by highlighting how family businesses can enhance competitiveness through innovation and sound financial strategies.